(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article discusses various ways to control the competence of oral communication of foreign students, analyzes the use of conventional and real tests, makes recommendations to verify the results of verbal communication. The problems of the control of speaking foreign students studying, analyzes the results of psychological preconditions teaching speaking. Prominent among the tests needed to monitor speaking given to testing and their components. Not every test can not display all the real-world results, it is therefore proposed test interviews showing the results of speaking, imitate real voice communication. In the article on the test guidelines, corresponding to different stages of testing. The attention is focused not only on the linguistic forms of expression, but also on the content. To test the results of speaking are invited to use interactive forms and dialogs polylog. Test presented in the article helps kontrolivaniyu results of oral communication.